2022
DOI: 10.1021/acs.iecr.2c01114
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Dispersed CaCO3 Nanoparticles in a Novel Membrane Dispersion Microreactor by a Chemical Coprecipitation Process

Abstract: A chemical coprecipitation method has been developed for the preparation of CaCO 3 nanoparticles using a novel membrane dispersion microreactor with calcium chloride, sodium carbonate, and calcium hydroxide as the reagents. Compared with the traditional coprecipitation process in a stirred tank reactor, a novel membrane dispersion microreactor has been developed, which makes it easier to control the crystal size. The effects of supersaturation, reaction time, feed flow rate, and reaction temperature on the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Also, peaks at 32.2°, 37.4°, 53.9°, and 67.5° were ascribed to the (111), (200), (220), and (222) of the calcium oxide (CaO) 23 . Furthermore, the peaks at 18.0°, 34.0°, and 47.0° were observed, corresponding to the (001), (101), and (102) of the calcium hydroxide (Ca(OH) 2 ) and peaks at 23.0°, 29.3°, and 39.4° corresponded to the (012), (104), and (113) of the calcium carbonate (CaCO 3 ) 24 , 25 . Based on this XRD analysis, it is evident that the PAC contains various crystalline calcium compounds as impurities.…”
Section: Resultsmentioning
confidence: 97%
“…Also, peaks at 32.2°, 37.4°, 53.9°, and 67.5° were ascribed to the (111), (200), (220), and (222) of the calcium oxide (CaO) 23 . Furthermore, the peaks at 18.0°, 34.0°, and 47.0° were observed, corresponding to the (001), (101), and (102) of the calcium hydroxide (Ca(OH) 2 ) and peaks at 23.0°, 29.3°, and 39.4° corresponded to the (012), (104), and (113) of the calcium carbonate (CaCO 3 ) 24 , 25 . Based on this XRD analysis, it is evident that the PAC contains various crystalline calcium compounds as impurities.…”
Section: Resultsmentioning
confidence: 97%
“…The results indicated the presence of amorphous silica in the sample, seen as a continuous elevation in the 2θ range from 10° to 35° [ 96 ]. Moreover, the results provided evidence for the presence of impurities in the biosilica sample: the pattern revealed the presence of calcium carbonate in the form of both vaterite and calcite [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three stages could be distinguished in the TGA curve: the first one is related to the release of adsorbed water, the second one came from the decomposition of organic residue [ 98 ], and the third one indicates the decomposition of carbonaceous salts [ 98 , 99 , 100 ]. A more precise search revealed that the analysed sample probably had a significant amount of CaCO 3 , as the mass loss in the characteristic temperature range (590–740 °C) was 34.8% [ 97 ]. A further decrease in the mass at higher temperatures may come from the dehydration of the silanol groups.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, the peaks at 18.0°, 34.0°, and 47.0° were observed, corresponding to the (001), (101), and (102) of the calcium hydroxide (Ca(OH) 2 ) and peaks at 23.0°, 29.3°, and 39.4° corresponded to the (012), (104), and (113) of the calcium carbonate (CaCO 3 ). 22,23 Based on this XRD analysis, it is evident that the PAC contains various crystalline calcium compounds as impurities.…”
Section: Characterization Of Pacmentioning
confidence: 93%